Orçamento democrático: implicações e repercussões no incremento da cidadania - Barbosa, Carolina de Brito (2013)
The global scenario, in recent times, has been reflecting economic and political changes that alter the way how the most diverse social and political agents interact. The need for expansion of the democracy, increasingly accentuated, in the search for the incorporation of social actors in political processes, legitimized not only by formal vote, but also in a real relationship with the popular will, gives emphasis to participatory democracy. Studies have emphasized that this practice can be considered as an effective method to rescue and practice of citizenship, from the expansion of the existing relationship between State and civil society, strengthening the Democratic State of Law. Since the promulgation of the Federal Constitution of 1988, Brazil began to deal with new forms of participation in political decisions. This new democratic model develops participatory practices, such as the democratic budget - a tool that aims to democratize public spaces, valorizing the participation, by granting the citizen the opportunity to opine, debate and deliberate on matters relating to public expenditures. In this way, the experience of participatory management, from the institution of the democratic budget and its contribution while propelling element of citizenship, is the object of our study. This work aims to contribute to the discussions on popular participation and effectuation of the citizenship, from the appropriation of the operating mechanisms of the State by the actors of the civil society, addressing issues regarding citizenship, popular participation and democratic budget. The hypothesis is based on the contribution that the democratic budget has to the expansion of the citizenship of portions of citizens that participate in this process, stimulating the social actors learning, from the insertion in spaces of social participation, as the democratic budget, collaborating with the realization of a more active and participatory citizenship. For the development of the research, it was used the qualitative methodology, and as a research technique, it was used the bibliographic research. This study seeks to reflect on the possibility of the democratic budget rescue the effectiveness of democracy, returning to the concept of citizenship and popular sovereignty, based on the idea of citizen participation in the affairs of community s interest.